Clinical and ElectrophysiologicAspects of Guillain Barre Syndrome among Children: Experience at Referral Tertiary Care Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Guillain Barre Syndrome (GBS) is an acute polyradiculopathy which is quite common in all ages.Objective: The aim of this study was to evaluate the clinical and electrophysiologicaspects of Guillain Barre Syndrome (GBS) in children.Methodology: This cross-sectional study was carried out in the Department of Neurophysiology of National Institute of Neurosciences and Hospital, Bangladesh from July 2016 to June 2018. Patients under 18 years of age fulfilling Brighton diagnostic criteria for GBS were included in this study. These patients were evaluated by detailed history, physical examination, and electrophysiological findings.Results: A total of 82 patients of GBS were enrolled in this study. The mean age was 12.93± 5.02 years (range 1 to